Forecasting wheat production in Syria using ARIMA models - معلا سلمان (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aimed at an analytical study of the reality of wheat production in Syria during the period 1991-2022 and its development during that period, after analyzing the time series expressing the development of wheat production quantities, studying their stability, and then predicting production quantities using ARIMA models. Among the obtained results: - The time series of wheat production in Syria during the period (1990-2021) is an unstable series due to the existence of a general trend. - The model ARIMA (1,2,0) suitable for forecasting wheat production in Syria was reached. It is a model whose features are significant and its determination coefficient is strong (the model is effective). Through it, wheat production in Syria was predicted until 2025. - Decrease in wheat production according to the proposed model, as the predicted production in 2025 reached 2050.64 thousand tons.